Teaching English Vocabulary to SD 257 Patampanua Students Using Scavenger Hunt - Nur Zarimah; Kalsum Kalsum (JELITA, 2024)
This study aims to explore the effectiveness of teaching English vocabulary through the scavenger hunt game in improving English vocabulary to students. The scavenger hunt game, which involves students in the search for new words in their environment, is thought to increase students' interest and involvement in learning a foreign language The methodology used in this study is to use quantitative research with exsperimental design. The participants of this study are grade IV students of SD 257 Patampanua which totals 13 students. Data from this study were collected by pre test and post test. The results indicated that teaching vocabulary to students through Scavenger Hunt, this has a positive effect on students' vocabulary and it is proven by the increase in the average score of students in the pre-test (47.76) and post-test (74.23), while the t-test score (1.87) is greater than the t-table (1,753). Thus, the game of scavenger hunt can be considered an effective and fun alternative in teaching English vocabulary. The study also suggests conducting further research with larger samples and variations of learning contexts to corroborate these findings.